We apply Euler's relation
e^(itheta)=costheta+isinthetaeiθ=cosθ+isinθ
e^(1/12pii)=cos(1/12pi)+isin(1/12pi)e112πi=cos(112π)+isin(112π)
e^(9/8pii)=cos(9/8pi)+isin(9/8pi)e98πi=cos(98π)+isin(98π)
cos(1/12pi)=cos(1/3pi-1/4pi)cos(112π)=cos(13π−14π)
=cos(1/3pi)cos(1/4pi)+sin(1/3pi)sin(1/4pi)=cos(13π)cos(14π)+sin(13π)sin(14π)
=1/2*sqrt2/2+sqrt3/2*sqrt2/2=12⋅√22+√32⋅√22
=(sqrt2+sqrt6)/4=√2+√64
sin(1/12pi)=sin(1/3pi-1/4pi)sin(112π)=sin(13π−14π)
=sin(1/3pi)cos(1/4pi)-sin(1/4pi)cos(1/3pi)=sin(13π)cos(14π)−sin(14π)cos(13π)
=sqrt3/2*sqrt2/2-sqrt2/2*1/2=√32⋅√22−√22⋅12
=(sqrt6-sqrt2)/4=√6−√24
cos(9/8pi)=cos(pi+1/8pi)cos(98π)=cos(π+18π)
=cos(pi)cos(1/8pi)-sin(pi)cos(1/8pi)=cos(π)cos(18π)−sin(π)cos(18π)
=-1*cos(1/8pi)-0*cos(1/8pi)=−1⋅cos(18π)−0⋅cos(18π)
=-cos(1/8pi)=−cos(18π)
Cos(2x)=2cos^2x-1cos(2x)=2cos2x−1
cos^2x=(1+cos(2x))/2cos2x=1+cos(2x)2
cos^2(pi/8)=1/2(1+cos(pi/4))=1/2(1+sqrt2/2)=(2+sqrt2)/4cos2(π8)=12(1+cos(π4))=12(1+√22)=2+√24
cos(pi/8)=sqrt(2+sqrt2)/2cos(π8)=√2+√22
cos(9/8pi)=-sqrt(2+sqrt2)/2cos(98π)=−√2+√22
sin(9/8pi)=sin(pi+1/8pi)=sin(pi)cos(1/8pi)+sin(1/8)picos(pi)sin(98π)=sin(π+18π)=sin(π)cos(18π)+sin(18)πcos(π)
=0-sin(1/8pi)=0−sin(18π)
cos^2(1/8pi)+sin^2(1/8pi)=1cos2(18π)+sin2(18π)=1
sin^2(1/8pi)=1-(sqrt(2+sqrt2)/2)^2=(4-2-sqrt2)/4sin2(18π)=1−(√2+√22)2=4−2−√24
sin(1/8pi)=sqrt(2-sqrt2)/2sin(18π)=√2−√22
sin(9/8pi)=-sqrt(2-sqrt2)/2sin(98π)=−√2−√22
Therefore,
e^(1/12pii)-e^(9/8pii)=cos(1/12pi)+isin(1/12pi)-cos(9/8pi)+isin(9/8pi)e112πi−e98πi=cos(112π)+isin(112π)−cos(98π)+isin(98π)
=(sqrt2+sqrt6)/4+sqrt(2+sqrt2)/2+i((sqrt6-sqrt2)/4+sqrt(2-sqrt2)/2)=√2+√64+√2+√22+i(√6−√24+√2−√22)